2013
DOI: 10.1097/rct.10.1097/rct.0b013e3182951fe9
|View full text |Cite
|
Sign up to set email alerts
|

Focal Liver Lesion Classification and Characterization in Noncirrhotic Liver

Abstract: Apparent diffusion coefficient (by fitting procedures) better performs than do D and f in FLL classification, especially when its values are less than 1.30 or greater than 2.00 × 10  mm/s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…In our opinion, utilising ratio values theoretically nulls potential heterogeneity caused by covariates, leaving the ratio reflecting true difference between the lesion and background liver. This method had also been used in previous study to access hepatic lesions [ 18 ]. The use of lesion: background ADC ratio has also been described to assess prostate lesions on MRI [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our opinion, utilising ratio values theoretically nulls potential heterogeneity caused by covariates, leaving the ratio reflecting true difference between the lesion and background liver. This method had also been used in previous study to access hepatic lesions [ 18 ]. The use of lesion: background ADC ratio has also been described to assess prostate lesions on MRI [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of ADC values between a lesion and the background liver can potentially negate these external factors and provide a more accurate representation of change in the diffusion with respect to normal tissue. In an earlier study, ADC ratio values were found to have better sensitivity and specificity than stand-alone ADC values in the interpretation of hepatic malignancies [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“… 30 We did not consider fitted ADC and intravoxel incoherent motion (IVIM) theory, because of the retrospective nature of this study; however, these results are not dissimilar from those presented in another of our recent works (prospective and based on IVIM theory parameters and fitted ADC). 31 When including b = 0 s/mm 2 images in ADC, these values could be slightly higher (probably around 10%), because of the larger contribution of perfusional IVIM in ADC.…”
Section: Discussionmentioning
confidence: 98%
“…Our study has three major limitations: first, it was a retrospective study so selection biases cannot be excluded and an overestimation of DwI accuracy in FLL classification and characterization is likely present, although not critical 31 ; second, during acquisition of Dw images cardiac motion artifacts and noise contamination might have distorted ADC values to a certain degree, in particular those of lesions located on the left lobe; third, both the ROI drawing and positioning on ADC map were highly operator-dependent so problems with reproducibility of the method should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that the D values can provided relatively high diagnostic performance in differentiating malignant from benign liver lesions [6] , [7] . But it was also found that there was great overlap of D between benign and malignant liver lesions [8] . Also, no significant differences in the perfusion-related parameters (i.e.…”
Section: Introductionmentioning
confidence: 99%